Bicuspid aortic valve patients show specific epigenetic tissue signature increasing extracellular matrix destruction. (9th September 2019) - Haunschild, Josephina; Schellinger, Isabel N; Barnard, Sarah J; von Aspern, Konstantin; Davierwala, Piroze; Misfeld, Martin; Petroff, David; Borger, Michael A; Etz, Christian D
Abstract: OBJECTIVES: Patients with a bicuspid aortic valve (BAV) have an increased risk for developing thoracic aortic aneurysm, which is characterized by the destruction of the elastic media of the aortic wall. Several important enzymes have been characterized to play key roles in extracellular matrix homeostasis, namely matrix metalloproteinases (MMPs). In this study, we investigated MMP-2 levels and their epigenetic regulation via the miR-29 family. METHODS: Aortic tissue samples from 58 patients were collected during cardiac surgery, of which 30 presented with a BAV and 28 with a tricuspid aortic valve. Polymerase chain reaction, western blot analysis and immunohistochemistry were performed to analyse MMP-2. In addition, enzyme-linked immunosorbent assay measurements were carried out to investigate both MMP-2 and tissue inhibitor of metalloproteinase-2 levels. To examine the epigenetic regulation of aortic extracellular matrix homeostasis, we furthermore studied the expression levels of miR-29 via qRT-PCR. RESULTS: Patients with a BAV were significantly younger at the time of surgery, presented significantly less frequently with arterial hypertension and displayed more often with an additional valvular disease. On a molecular level, we found that MMP-2 is increased on gene and protein level in BAV patients. Tissue inhibitor of metalloproteinase-2 levels do not differ between the groups. Interestingly, we also found that only miR-29A is significantly downregulated in BAVs. CONCLUSIONS: Our findings highlight the importance of MMP-2 in the context of extracellular matrix destruction in BAV patients. We present new evidence that miR-29A is a crucial epigenetic regulator of these pathomechanistic processes and might hold promise for future translational research.